2015
DOI: 10.1364/oe.23.000642
|View full text |Cite
|
Sign up to set email alerts
|

High confinement, high yield Si_3N_4 waveguides for nonlinear optical applications

Abstract: In this paper we present a novel fabrication technique for silicon nitride (Si(3)N(4)) waveguides with a thickness of up to 900 nm, which are suitable for nonlinear optical applications. The fabrication method is based on etching trenches in thermally oxidized silicon and filling the trenches with Si(3)N(4). Using this technique no stress-induced cracks in the Si(3)N(4) layer were observed resulting in a high yield of devices on the wafer. The propagation losses of the obtained waveguides were measured to be a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 18 publications
0
61
0
Order By: Relevance
“…For maximizing the waveguide-internal intensity via a strong confinement, enlarged core cross-sections are considered with a height and width around 1 µm. The two-dimensional step-index profile used for the calculations is based on the actual waveguide shape available from SEM images [13], which has slightly rounded edges at the bottom. Eigenmode calculations have shown that these rounded edges do not affect the polarization of the eigenmodes.…”
Section: Experimental Procedures and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For maximizing the waveguide-internal intensity via a strong confinement, enlarged core cross-sections are considered with a height and width around 1 µm. The two-dimensional step-index profile used for the calculations is based on the actual waveguide shape available from SEM images [13], which has slightly rounded edges at the bottom. Eigenmode calculations have shown that these rounded edges do not affect the polarization of the eigenmodes.…”
Section: Experimental Procedures and Resultsmentioning
confidence: 99%
“…This platform offers a unique combination of adjustable properties, i.e., record-low propagation loss (<0.001 dB/cm) [5] such as for high-Q resonators [11], a wide spectral range of optical transparency (from about 310 nm throughout the entire visible spectrum up to 5.5 µm [12]), and a high index contrast to achieve tight mode confinement. The latter is achieved with extremely thick waveguide cores, fabricated with a novel approach of stepwise filling of pre-etched grooves [13]. This platform has also reached a considerable degree of maturity, allowing two-dimensional tapering [14] for low-loss fiber coupling or realizing hybrid lasers [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this geometry, core widths of 0.8-1.0 μm and thicknesses varying from 0.8 to 1.2 μm were realized [53]. The waveguide channel is multimodal; up to three modes exist.…”
Section: Triplex Technology and Designmentioning
confidence: 99%
“…Although our demonstration did not integrate the nonlinear waveguide for photon pair generation on the same chip, recent progress has shown that it is possible to use Si3N4 nonlinear devices for photon pair generation [15], and such nonlinear devices can be made using the TriPlex technology [16]. In addition, a Si3N4 platform compatible with our circuit exhibits fast stressoptic effect at >1 MHz [17], indicating the potential of our circuit operating at much higher speed in the future for quantum information processing.…”
mentioning
confidence: 98%